Comparative proteomics reveals different protein expression in platelets in patients with alcoholic liver cirrhosis - Haji Begli, Nima; Freund, Cora; Weiss, Karl Heinz; Gotthardt, Daniel; Wannhoff, Andreas (Proteome science, 2024)
The role of platelets in disease progression as well as the function of platelets as part of the haemostatic and immunological system in patients with liver cirrhosis is only incompletely understood. This is partly due to difficulties in assessing platelet function. Proteome analyses of platelets have been used to further investigate the role of platelets in other diseases.
Gesehen am 16.08.2024